Social Harmony in the Glorious Quran and Ways to Achieve It - Shahad Munir Qawam Al-Deen Al-Klidar (Islamic Sciences Journal, 2025)
A careful examination of Quranic texts reveals a profound emphasis on social harmony, with a strong commitment to establishing its principles and values. The Glorious Quran fortifies this harmony with protective measures to safeguard it from any threats to its foundations, making it one of its significant objectives. Through its language and meanings, the Quran consistently underscores the importance of social harmony and the establishment of its pillars within society. Simultaneously, it strives to preserve and protect this structure from anything that might undermine or target it for destruction. The verses of the Glorious Quran encompass various meanings related to achieving social harmony. These meanings range from safety from harm and evil, encouragement for good praise, exchanging greetings among community members, reconciliation, and other similar concepts. Additionally, the Quran introduces synonymous terms for social harmony, such as security, tranquility, and peace, all of which advocate for harmony, cohesion, and unity among members of society.